Near-threshold high spin amplification in a 1300 nm GaInNAs spin laser. (1st August 2018) - Cemlyn, Ben; Adams, Mike; Harbord, Edmund; Li, Nianqiang; Henning, Ian; Oulton, Ruth; Korpijärvi, Ville-Markus; Guina, Mircea
Abstract: Using continuous-wave optical pumping of a spin-VCSEL at room temperature, we find high spin amplification of the pump close to threshold within the communications wavelength window, here at 1300 nm. This facilitates a strong switch from left to right circularly polarised light emission, which has potential applications in polarisation encoding for data communications. We use a simple spin flip model to fit the experimental results and discuss the VCSEL parameters that affect this amplification.